Bus rapid transit practitioner's guide (Report (Transit Cooperative Research Program) ;, 2007)
Introduction -- Planning framework -- Estimating BRT ridership -- Component features, costs, and impacts -- System packaging, integration, and assessment -- Land development guidelines.